Orkut e Facebook: as teias da memória em meio às redes sociais - Marcia Elisa Rendeiro (Ciências Sociais Unisinos, 2011)
We consider, in this current work, Orkut and Facebook fenomena by the analysis of memory in its narrative aspects and in the development of contemporary identities. We investigate the networks by the perspective of a collection of images, linked to its nature of a memory factory. We remind that, concerning the group of experiences in which the action of collecting generates, the satisfaction granted by the possession of objects and the value attached to them (either as an element of trade or just as something to be seen and admired) deserve to be on the spot. In this case, there has to be highlighted the presence of several elements: satisfaction and pleasure, exhibition, power and possession. In the dynamics composed by the social networks, with sites that allow you to find and "increase the amount" of friends by specific features, create discussion groups and transit among albums and communities; we foresee the existence of a circuit that oppose word and image, a text with specific narrative features, a kind of a virtual device that stimulates the generation of memories and representation - links of a same chain that serves to punctuate the writing of the social memory and the formation of new identities.